Differenzierungsmodell für eine anforderungsorientierte verkehrliche Kapazitätsplanung im ÖPNV. - Bergner, Ulrich (My University, 2018)
Die verkehrliche Kapazitätsplanung ist für ÖPNV-Unternehmen ein wichtiger Geschäftsprozess. Die Planungsergebnisse entscheiden maßgeblich über den Einsatz kostenträchtiger Ressourcen und über den Erfolg der ÖPNV-Dienstleistung am Verkehrsmarkt. Die Arbeit ermittelt die Anforderungen aller relevanten Anspruchsgruppen und benennt Umsetzungsdefizite der heutigen Planungspraxis. Diese Defizite bilden die Grundlage für die Entwicklung einer neuen, anforderungsorientierten Planungsmethodik. Für diese Methodik wird die Qualität des Platzangebotes aus der Perspektive der Kunden definiert und ermittelt. Aus Kundensicht stellt dabei eine uneingeschränkte Sitzplatzverfügbarkeit das höchste Qualitätsniveau dar, während die zulässige Mindestqualität von der kundenseitigen Akzeptanzgrenze für Qualitätsverluste durch Sitzplatzmangel bestimmt wird. Zur Bestimmung dieser Qualitätsverluste werden die Risikoparameter "Stehdichte", "Stehdauer" und "Stehplatzwahrscheinlichkeit" für sämtliche Linienabschnitte und alle Kundenfahrten einer Fahrplanfahrt ermittelt. Aus den detaillierten Ergebnissen lassen sich zielgerichtete Angebotsmaßnahmen ableiten, deren Realisierung eine bessere Erfüllung der Anforderungen der relevanten Anspruchsgruppen verspricht und Ansätze für ein stärker marktorientiertes Vorgehen bei der Angebotsgestaltung liefert.

Transport related capacity planning constitutes an important business process for public transport companies. Respective results have a crucial impact on the allocation of costly resources and on public transport services. Despite this significance, planning is mostly limited to implementing standards put forth by authorities thereby neglecting to address complementary customer and corporate needs. The paper determines relevant stakeholder requirements and depicts implementation deficits of current planning methods. Furthermore, these deficiencies allow for laying the foundation to develop a new requirement based planning methodology. Against this backdrop the quality of available space from a customer perspective is defined and derived. Moreover, from the aforementioned perspective the ample provision of available space is brought to focus while bearing a minimal customer based quality threshold - determined by loss of seating capacity - in mind. By applying all renowned standards pertaining to risk assessment relevant parameters such as standing density, - duration and -probability are determined for all customer related trips of a schedule. The aforementioned approach is based on realized trips in relation to an underlying stop-oriented origin-destination-matrix. Following dynamic characteristics of risk parameters en route the calculation results depict a stark variation in outcome as to loss of quality. Hence, a vivid picture attributed to customer's perceived seating quality emerges. In so far as an electronic fare management system is in place specific quality levels with regard to an underlying origin-destination-matrix based on assigned customer trips can be derived while also taking various market segments into consideration. Emphasis is laid upon a market-oriented approach bringing to focus enhanced services. Moreover, detailed results allow for deriving concise measures, which in turn improve compliance pertaining to relevant stakeholder requirements.
Differentiation model for requirement oriented planning of transportation capacity in local public transport.
Keywords: Verkehr; Verkehrsplanung; Kapazitätsplanung; ÖPNV; Verkehrsmittel; Verkehrsunternehmen; Planungspraxis; Planungsmethode; Sitzplatz; Verfügbarkeit; Platzangebot; Qualität; Akzeptanz; Kunde; Kundenorientierung; Fahrgast; Fahrgastbefragung